24.9k views
3 votes
Please help, and then u need factor the expression

Please help, and then u need factor the expression-example-1
User Peet
by
5.1k points

1 Answer

4 votes

Answer: Choice A

U = (x+3)

V = 7

===========================================

Step-by-step explanation:

If we let U = (x+3), then the original expression turns into U^2 + 14U + 49

This factors to (U+7)^2 when using the perfect square factor rule which in general is (a+b)^2 = a^2+2ab+b^2

Comparing the last term 49 with b^2, we see that b^2 = 49 leads to b = 7

So that must mean V = 7 in order to have

(U+V)^2 = U^2+2UV+V^2 = U^2 + 14U + 49

be a true statement

User Jarrett Meyer
by
5.5k points